2018
DOI: 10.1016/j.jvs.2017.07.141
|View full text |Cite|
|
Sign up to set email alerts
|

Registry Assessment of Peripheral Interventional Devices (RAPID): Registry assessment of peripheral interventional devices core data elements

Abstract: Ultimately, we hope this work will facilitate and improve device evaluation and surveillance for patients, clinicians, health outcomes researchers, industry, policymakers, and regulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…The current state of evaluating endovascular devices to treat patients with PAD is costly and difficult due to the heterogeneity of the disease and the multiple specialties that perform endovascular therapy on these patients. 33 This has spurred initiatives by the FDA to support peripheral endovascular therapy registry efforts and potential use of real-world evidence in FDA regulatory submissions and postmarket surveilance. 33,34 The LIBERTY registry provides a framework and an example for these initiatives going forward.…”
Section: Discussionmentioning
confidence: 99%
“…The current state of evaluating endovascular devices to treat patients with PAD is costly and difficult due to the heterogeneity of the disease and the multiple specialties that perform endovascular therapy on these patients. 33 This has spurred initiatives by the FDA to support peripheral endovascular therapy registry efforts and potential use of real-world evidence in FDA regulatory submissions and postmarket surveilance. 33,34 The LIBERTY registry provides a framework and an example for these initiatives going forward.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with lifestyle-limiting claudication, revascularization (ie, surgical or endovascular) and exercise are superior to medical management alone in terms of quality of life. 21,22 Our study showed that patients with RC 2-3 symptoms undergoing endovascular therapy had a 98.5% 36-month freedom from major amputation and a VascuQoL total score of 5.3±1.4, suggesting that it would be reasonable to intervene early in claudicants, when they have failed medical and/or exercise therapy, in order to improve their quality of life.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, large peripheral endovascular therapy registries should be created for more accurate post-market surveillance. 22 Propensity score outcome data from retrospective comparisons showed that atherectomy was statistically superior to balloon angioplasty, stenting, and bypass surgery in a cohort of 36,000 patients with CLTI over the course of 4 years. 53 As we continue to evaluate different treatment modalities in prospective and retrospective analyses, the outcomes are pointing toward a favorable long-term benefit when CLTI patients are treated early rather than late, especially when the treatment includes atherectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Similar work has been reported by the Registry Assessment of Peripheral Arterial Devices (RAPID) group for multispecialty collaboration within USA. 17,18 The ICVR-recommended data set has many agreements with data elements and definitions in RAPID, which is focused on device evaluation for peripheral vascular intervention in USA. The current ICVR database recommendations extend those of RAPID to encompass both open and endovascular revascularisation and for international studies, while still allowing device evaluation.…”
Section: Discussionmentioning
confidence: 99%